IMPLEMENTASI PENGEMBANGAN E-MODUL BIMBINGAN TEKNIS BERBASIS CANVA UNTUK PANITIA PENGAWAS PEMILU KECAMATAN DI BAWASLU KABUPATEN SERANG - Abdurrohman Abdurrohman; Isti Rusdiyani; Lukman Nulhakim (Akademika : Jurnal Teknologi Pendidikan, 2023)
This study aimed to evaluates the implementation of a Canva-based technical guidance e-module in Panwascam, the District Election Supervisory Committee, under the supervision of Bawaslu in Serang Regency. Developed following the ADDIE model, the digital e-module includes relevant materials on election supervision procedures, handling election violations, and reporting techniques. Research and Development (R&D) methodology is employed to validate and refine the module. The study involves 29 Panwascam members as respondents. Results demonstrate the effectiveness of the Canva-based e-module in enhancing the knowledge and skills of Panwascam in performing election oversight tasks. In conclusion, the Canva-based e-module proves effective in improving Panwascam's knowledge and skills within Bawaslu Kabupaten Serang, providing a viable training alternative for hard-to-reach areas while enhancing accessibility and efficiency in delivering training materials.